Piezoelectric energy harvesting with a nonlinear energy sink. (February 2017) - Zhang, Yu; Tang, Lihua; Liu, Kefu
This article presents a novel piezoelectric energy-harvesting device. Different from the existing designs in the literature, the proposed device is based on the principle of nonlinear energy sink in order to achieve simultaneous broadband energy harvesting from the nonlinear energy sink and vibration suppression for the primary structure. First, the concept of the proposed design is described. Subsequently, system modeling and parameter identification are addressed. The performance of the apparatus under transient responses is examined through both numerical simulation and experimental study. The results show that the proposed apparatus behaves similarly as the nonlinear energy sink with the following features: 1:1 resonance, targeted energy transfer, initial energy dependence, and so on. Broadband voltage output is achieved when the nonlinear energy sink is activated.